Does School Gardening and Nutrition Education Improve Knowledge and Fruit-Vegetable Consumption Among Elementary School Students? - Fitriani, Anna; Linda, Ony; Aslam (Universitas Airlangga, 2023)
Background: Although scientific evidence has revealed the benefits of fruit and vegetable consumption (FVC) for children, 96.8% of age school children in Indonesia and 70.6% of primary school students in Jakarta did not have FVC as recommended. Aims: to assess how Muhammadiyah Elementary School Students' knowledge and FVC were affected by school gardening and nutrition education. Methods: Following 6 monthly program, knowledge and FVC were assessed by using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and knowledge questionnaire. Results: 1) There is a significant increase in students' knowledge scores from 43.24 ± 14.24 to 70.31 ± 18.92 (P-value 0.000). 4); 2) The mean of FCV was elevated from 211.45±12.33 to 289.76±19.64, however, it was not statistically significant (P-Value of 0.058). Conclusion: Although knowledge has been improved following 6 months program, the FVC level was not dramatically enhanced. Future similar activities need to be done in a non-pandemic situation and should be lengthened into more than 6 months to portray a significant increase in FVC.